Community Empowerment through Sharia Bank-Based Investment Programs: A Case Study in the Ampel Region - Ilma, Adam Zidni; Oktafia, Renny (PT Inovasi Pratama Internasional, 2025)
This service aims to empower communities in the Ampel area through a sharia bank-based investment program, with a participatory approach that involves active community involvement in implementing sharia principles in their economic activities. The methodology used includes several important stages. First, the needs and characteristics of the Ampel community were identified, including business capital, education, health and housing needs, as well as investment preferences for sharia products such as sharia deposits, sharia microfinancing and waqf or sukuk-based investments. This stage involves in-depth data collection to understand people's primary financial needs. After identification, an empowerment program is designed with the aim of improving the economic welfare of the community through sustainable sharia bank investment. This program emphasizes active community participation in sharia financial and investment management, developing strategies that prioritize justice, transparency and sustainability. Furthermore, outreach was carried out to introduce the importance of sharia investment to the public. This socialization aims to increase public understanding and participation in using sharia financial products and services. Program implementation is carried out through several stages involving various stakeholders, with a structured approach to ensure its success and sustainability. This program has succeeded in increasing financial literacy, access to sharia financial products, and the economic independence of the Ampel community. The results show that a participatory approach in sharia investment can provide significant social and economic benefits, and has the potential to become a model of sharia-based economic empowerment that can be applied in other regions. With continued support, it is hoped that this program will continue to develop and provide greater benefits for the Ampel community.